The Evidance Based Nursing Practice: Application of Diabetes Self-Management Education to Lowering Blood Sugar Levels in the Elderly - Prakoso, Adi Bayu; Khasanah, Uswatul; Anggraini, Dewi; Nurhayati, Nurhayati (Indonesian Journal of Global Health Research, 2024)
Diabetes Mellitus is a collection of symptoms caused by high levels of glucose in the blood and is a chronic disease that can be experienced by the elderly due to a poor lifestyle and irregular eating patterns. Objective: This research aims to identify one Diabetes Self-Management Education article as a source of evidence that has quality so that it can be applied to reduce blood sugar levels in the elderly and determine its effect on elderly people with diabetes mellitus. Methode: The strategy used in this research is a quasi-experiment without control carried out with a one group pretest posttest design. The sample used in this study was 13 elderly people who had diabetes mellitus. Researchers use sample criteria to determine samples in research according to inclusion and exclusion criteria. Result: The results of the analysis using the Wilcoxon test showed that there was a difference in blood glucose levels in the elderly before and after implementing Diabetes Self-Management Education is p = 0.001, which means it has statistical significance. Conclusion: This research shows that implementing Diabetes Self-Management Education can reduce blood glucose levels in the elderly.